How many Layers has the Adventitia? – Structure of the Arterial Tunica Externa Revisited. (10th June 2016) - Witter, K.; Tonar, Z.; Schöpper, H.
Summary: Tunica adventitia or tunica externa is the outer layer of the blood vessel wall. It consists of connective tissue with vasa and nervi vasorum and plays a key role in vascular health. The aim of our study was to compare the wall layers beyond tunica media in arteries of different type and location. The following arteries of pig, dog and cat were processed histologically and analysed by light microscopy: aorta ascendens, arcus aortae, aorta thoracica, aorta abdominalis, arteria (a.) femoralis, a. tibialis cranialis, a. carotis communis, a. lingualis, a. basilaris, a. cerebralis media, a. testicularis and aa. jejunales. We found two layers of connective tissue outside the media: (1) a compact layer with many elastic fibres in muscular and few in elastic arteries and (2) an outer layer of loose connective tissue. The compact layer was missing in aorta ascendens, arcus aortae and intracranial vessels. Adventitial stripping removed only the loose connective tissue layer. In spite of the still present compact layer, stripped arteries were very flimsy. We suggest using the term 'tunica externa' for the compact connective tissue layer and 'tunica adventitia' for the outermost loose connective tissue layer as in other organs. The presence of the tunica externa differs between species, arteries and arterial side, as well as the removability of tunica adventitia and tunica externa by anatomical dissection.